IMPLEMENTASI STRATEGI PEMASARAN DALAM MENINGKATKAN KUANTITAS SANTRI DI MASA PANDEMI (STUDI KASUS DI PONDOK MODERN UMMUL QURO AL – ISLAMI) - Alamsyah, Ilham; Misno; Waki, Ahmad (Institut Agama Islam Sahid Bogor, 2024)
There are many words or terms of Islamic Economic in the instructions compilation of National Sharia Board – Indonesia Council of Ulama in Arabic. The instruction of National Sharia Board – Indonesia Council of Ulama is a law product that is published as the first step of National Sharia Board – Indonesia Council of Ulama in socializing the instructions of National Sharia Board and the Islamic Economic in general. The goals of the research are (1) analizing the absorption standard from Arabic language into Indonesian in the instructions of National Sharia Board (2) Analizing the terms absorbed from Arabic language into Indonesian in the instructions of National Sharia Board that are standarded in The Great Dictionary of the Indonesian Language. This research uses Match Method as the data analysing technique. Match method is a way to analyze data in answering the problem researched with determining tool comes from outside the language. The result of the research shows that the absorption standard from Arabic language into Indonesian in the instructions of National Sharia Board – Indonesia Council of Ulama through the following steps, 1) selection, 2) codification, 3) function description, 4) agreement. The research found that there are 20 Islamic Economic terms in Indonesian which are absorbed from Arabic language in the instructions of National Sharia Board – Indonesia Council of Ulama about the contract standarded in The Great Dictionary of the Indonesian Language, the fifth edition. Those are Akad, Istisna’, Salam, Wadi’ah, Wakalah, Musyarakah, Ijarah, Mudharabah, Murabahah, Hibah, Shahibul maal, Mudharib, Muwwakil, Kafil, Sukuk, syarik, Wa’d, Riba, Ikhtikar, Gharar Islamic religious tertiary institutions are expected to produce graduates who are qualified and have an entrepreneurial spirit who are able to create jobs. Likewise, an Islamic educational institution, in this case the Private Islamic Religious College (PTKIS), especially the Bogor Sahid Islamic Institute (INAIS), must continue to strive to improve quality in an effort to maintain its existence and survive amidst the very tight competition in the world of education today. . To achieve these ideal conditions, higher education institutions in general and in this case INAIS must clearly have a vision and mission that are in line with today's, tomorrow's and future needs. The purpose of this study is to analyze the Vision and Mission of the Sahid Islamic Institute in Creating an Islamic Entrepreneurial University. The type of research used is qualitative research with a descriptive analytical case study approach and library research. The results in the study show that the Vision and Mission of the Sahid Islamic Institute in Creating an Islamic Entrepreneurial University has not been fully achieved because there are obstacles faced by the Sahid Islamic Institute, one of which is because there are many graduate or alumni professions who are not entrepreneurs so that a strategy is needed, namely to improve education. and teaching, research and community service as well as supported by infrastructure that supports the achievement of entrepreneurial competence. Keywords: Strategy, Sharia Marketing, Increasing Quantity, Pandemic Period